2020
DOI: 10.5530/pj.2020.12.121
|View full text |Cite
|
Sign up to set email alerts
|

The Nephroprotective And Antioxidant Activity of Sterculia rubiginosa Zoll. Ex Miq. Leaves

Abstract: Background: Sterculia has an antioxidant activity. The Sterculia genus has phenols and flavonoids content, and this chemical content may be have an nephroprotective activity. Objective: The study was to investigate the in vitro study of antioxidant activity with DPPH and FRAP study and nephroprotective activity of Sterculia rubiginosa Zoll. Ex Miq. Leaves extract. Materials and Methods: The leaves was extracted using ethanol. This extract was determined for antioxidant activity by in vitro study with DPPH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The determination of the levels of secondary metabolites in the leaf extract showed that the most numerous groups of phenolic compounds were tannins and flavonoids, with values of 72.16 and 28.66% w/w. Previous studies showed that phenolics and flavonoids were the most important secondary metabolites in the genus Sterculia [32].…”
Section: Phytochemical Analysismentioning
confidence: 97%
“…The determination of the levels of secondary metabolites in the leaf extract showed that the most numerous groups of phenolic compounds were tannins and flavonoids, with values of 72.16 and 28.66% w/w. Previous studies showed that phenolics and flavonoids were the most important secondary metabolites in the genus Sterculia [32].…”
Section: Phytochemical Analysismentioning
confidence: 97%
“…Starting from screening to look for active compounds, then continued with testing the effectiveness or selectivity and its mechanism of action in experimental animals or microbes, after being declared to have certain pharmacological activities by a series of safety tests on experimental animals, the toxicity test 17 . In previous studies, Ki Hampelas leaves have activity as a nephroprotective and antioxidant with a minimum dose of 50 mg/kg 16 . So it is necessary to do a toxicity test to ensure the safety of Ki Hampelas leaves extract.…”
Section: Introductionmentioning
confidence: 98%
“…The antioxidant activity and total flavonoids equivalent to quercetine 17 . So it is interesting to study whether Sterculia rubiginosa has antioxidant and nephroprotective activity 16 .…”
Section: Introductionmentioning
confidence: 99%